ANALISIS RISIKO USAHATANI JAMUR MERANG DI KECAMATAN CILAMAYA KULON KABUPATEN KARAWANG - Kiki Sasmita; Abubakar Abubakar; Luthfi Nur’azkiya (Universitas Galuh, 2022)
Mushroom is one of the leading vegetable commodities that are widely cultivated in Karawang Regency. The aims of this study were 1) to determine the risks faced by mushroom farmers and how the risks to production, prices and incomes 2) farmers' perceptions of risk in Cilamaya Kulon District, 3) how farmers faced risks. The method used is descriptive analytic. This research was conducted in Cilamaya Kulon sub-district which is spread across the villages of Pasirukem, Pasirjaya and Muktijaya. The data analysis used is descriptive analysis to describe the types of risk and how farmers face risk, quantitative analysis to measure production risk, price and opinion by using the coefficient of variation. and analysis of farmers' perceptions which were measured using a Likert scale. The results showed that the types of risks faced by mushroom farmers in Cilamaya Kulon District were: production risk, namely poor seed quality, price/market risk, namely fluctuating selling prices, institutional risk, namely no agricultural extension workers, human risk, namely reduced labor. work, the financial risk is the small amount of capital owned by farmers. Farmers have a good perception of risk because they think the risks that occur are not too disturbing. Farmers' ways of dealing with risk are: Before farmers start farming, farmers make plans with farmer groups. During the production period, farmers adjust the temperature in the mushroom kumbung so that the temperature is maintained. After experiencing the risk, farmers continue to farm mushroom and look for other jobs to get additional income.